2009
DOI: 10.1007/s11306-009-0161-7
|View full text |Cite
|
Sign up to set email alerts
|

ω-3 oil intake during weight loss in obese women results in remodelling of plasma triglyceride and fatty acids

Abstract: Previous studies have shown that a combination of weight loss and fish oil supplementation reduce cardiovascular disease and diabetes risks by increasing adiponectin and reducing triacylglyceride concentrations, while weight loss alone significantly improves insulin sensitivity and reduces inflammation. Here, a metabolomic approach, using a combination of 1H-Nuclear Magnetic Resonance spectroscopy, and gas and liquid chromatography and mass spectrometry, was employed to elucidate the metabolic changes in blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…For the three experiment groups, a comparison analysis generated a PLS-DA model with R 2 Y = 0.867 and Q 2 = 0.679, displaying the faithful representation and excellent predictive capacity, respectively. A robust model was linked to a Q 2 value > 0.40 (McCombie et al 2009). In fact, this was the case for this study.…”
Section: H Nmr Spectroscopic and Pattern Recognition Analysismentioning
confidence: 99%
“…For the three experiment groups, a comparison analysis generated a PLS-DA model with R 2 Y = 0.867 and Q 2 = 0.679, displaying the faithful representation and excellent predictive capacity, respectively. A robust model was linked to a Q 2 value > 0.40 (McCombie et al 2009). In fact, this was the case for this study.…”
Section: H Nmr Spectroscopic and Pattern Recognition Analysismentioning
confidence: 99%
“…A study by Lankinen et al (2009) [7] found that serum bioactive lipids associated with insulin signaling and inflammatory pathways, ceramides, lysophosphatidylcholines (lysoPCs) and diacylglycerols were decreased by fatty fish intake. Furthermore, McCombie et al (2009) [8] found that fish oil supplementation in conjunction with body weight loss reduced total plasma TG content; in addition, weight loss without fish oil supplementation decreased the levels of plasma docosapentaenoic acid (22:5). Overall, only a limited number of clinical studies have been conducted on the impact of n-3 PUFA on the metabolome.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of special diets on the metabolic pattern was also examined in a study on weight loss [69] . Three test groups of 31 women each were given ω -3-fish oil or a placebo over 24 weeks.…”
Section: Metabolomicsmentioning
confidence: 99%